HEAVY METALS IN TOMATO, BELL PEPPER AND ONION PRODUCED UNDER THE KANO RIVER IRRIGATION PROJECT - Abdullahi, N.; Dandago, M. A.; Gambo, M. S.; Sarki, S. A.; Idah, P. G. (FUDMA JOURNAL OF SCIENCES, 2023)
The presence of heavy metals (HMs) in food crops is an issue of public health significance, which is progressively evolving into a worldwide predicament. The continuous discharge of HMs into the environment through a range of anthropogenic practices and natural occurrences has raised concerns regarding food safety and human well-being. HMs exhibit substantial resistance and when they infiltrate the food chain, they establish a sustainable cycle within the food web. Samples of Tomato, Bell pepper and Onion were taken from 10 different locations across the irrigation scheme. Concentrations of Zn, Pb, Cd, Ni, Co, Cu, Cr and Hg were determined in Tomato, Bell pepper, Onion bulb and Onion leaf samples. The mean concentrations of Zn, Pb, Cd, Ni, Co, Cu, Cr in Tomato are 2.437, 0.869, 0.367, 1.325, 0.649, 2.090, 15.255 mg/kg respectively. Average concentrations of these HMs in Bell pepper are 3.713, 1.225, 0.361, 1.619, 0.382, 3.071, 9.279 mg/kg respectively. While in Onion bulb are 4.123, 0.878, 0.282, 2.438, 1.175, 5.848, 28.219 mg/kg respectively. Mean concentrations observed in Onion leaves are 3.697, 1.001, 0.716, 1.145, 1.017, 1.191, 10.993 mg/kg for Zn, Pb, Cd, Ni, Co, Cu, Cr respectively. The orders for HMs accumulations in vegetables are Cr>Zn>Cu>Ni>Pb>Co>Cd for Tomato and Bell pepper samples, Cr>Cu>Zn>Ni>Co>Pb>Cd for Onion bulb and Cr>Zn>Cu>Ni>Co>Pb>Cd for Onion leaves. Hg was not detected in all the vegetable samples. The mean concentrations for Zn, Cd and Cr exceeded permissible limits in all the vegetable samples.
Keywords: Heavy metals; vegetables; food contamination; food safety; human health